2012
DOI: 10.1177/1352458512440060
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of an elastase inhibitor in a neuromyelitis optica-like disease driven by a peptide of myelin oligodendroglial glycoprotein

Abstract: Background The pathology of neuromyelitis optica (NMO), in contrast to multiple sclerosis, comprises granulocyte infiltrates along extensive lengths of spinal cord, as well as optic nerve. Furthermore, IFN-β treatment worsens NMO. We recently found that experimental autoimmune encephalomyelitis (EAE) induced with Th17 cells is exacerbated by IFN-β, in contrast to disease induced with Th1 where treatment attenuated symptoms. Objective This study demonstrates the similarities between NMO and Th17 EAE and how n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 37 publications
5
71
0
1
Order By: Relevance
“…It was reported that Sivelestat, a neutrophil elastase inhibitor, reduced the expression of cytokines IL-17, IL-5, and IL-2 in Th17-induced EAE, which is thought to be analogous to NMO [66,125].…”
Section: Future Perspectivesmentioning
confidence: 98%
“…It was reported that Sivelestat, a neutrophil elastase inhibitor, reduced the expression of cytokines IL-17, IL-5, and IL-2 in Th17-induced EAE, which is thought to be analogous to NMO [66,125].…”
Section: Future Perspectivesmentioning
confidence: 98%
“…Of note, tolerance to MOG and other myelin autoantigens is not governed by the same mechanisms (31,32 (33). Of particular interest, a form of neuroinflammation resembling NMO that is negative for antibody to AQP4, seen in a small proportion of clinical cases of NMO, is driven by immunity to MOG (17).…”
Section: Our Observations That Aqp4-specific Th17 Cells From Aqp4mentioning
confidence: 99%
“…Cinryze therapy was safe and associated with disability improvement to preattack levels in 9/10 patients after 1 month. Finally, inhibition of neutrophil elastase with sivelestat was beneficial in animal models of NMOSD [55,56], and a small open-label trial evaluating sivelestat for NMOSD attacks is currently being conducted in Japan.…”
Section: Treatment Of Nmosd Attacksmentioning
confidence: 99%